The Evaluation of Health Literacy Interventions for Palliative Care Patients - Farida Nur Qomariyah; Ika Adelia Susanti (KHD Production, 2025)
Health literacy is crucial in palliative care, where patients often face complex medical conditions and must make end-of-life decisions. This literature review aims to evaluate the effectiveness of health literacy interventions in improving patient outcomes in palliative care settings. The review synthesized evidence from high-quality studies, including randomized controlled trials (RCTs) and quasi-experimental designs, with a focus on various intervention strategies such as educational programs, multimedia tools, and health coaching. The review utilized the PRISMA framework for study selection and the JBI critical appraisal checklist for assessing study quality. It included studies from databases such as Scopus, PubMed, and Google Scholar, focusing on publications from 2016 to 2025. The studies consistently showed that these interventions enhance patient understanding, engagement in treatment decisions, and overall quality of life. However, challenges remain in identifying the most effective interventions due to variations in study designs and outcome measures. This review highlights the significance of health literacy interventions in palliative care, advocating for additional research that focuses on LHL-specific strategies and standardized outcome measures to improve patient care.